Analisis Pengaruh Motivasi dan Kepuasaan Kerja Terhadap Kinerja Karyawan Pada Jne Lubuk Begalung Padang - Nadilla Silva Fitri; Muhammad Iqbal; Niati Syafputri; Nurul Fadhilah; Vivi Nila Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
This Community Service aims to determine the influence of motivation and job satisfaction on employee performance at JNE. Job satisfaction is the attitude of workers towards their work, which arises based on an assessment of the work situation. Factors that influence job satisfaction or dissatisfaction are: type of work, coworkers, benefits, fair treatment, job security, opportunities to contribute ideas, salary/wages, performance recognition, and opportunities for growth. The aim of this research is to determine the importance of implementing motivation and job satisfaction at JNE. This article was prepared by observing and collecting data. The results of this research show that motivation and job satisfaction at JNE are very important to obtain maximum work results in the future.